2020
DOI: 10.1021/acsnano.9b08587
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Membrane Biomimetic Magnetic Nanocarriers for Targeted Delivery and in Situ Generation of Nitric Oxide in Early Ischemic Stroke

Abstract: Early diagnosis and treatment of acute ischemic stroke poses a significant challenge due to its suddenness and short therapeutic time window. Human endogenous cells derived biomimetic drug carriers have provided new options for stroke theranostics since these cells have higher biosafety and targeting abilities than artificial carriers. Inspired by natural platelets (PLTs) and their role in targeting adhesion to the damaged blood vessel during thrombus formation, we fabricated a biomimetic nanocarrier comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
173
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 37 publications
0
173
0
Order By: Relevance
“…Meanwhile, PDT uses the photosensitizers to generate singlet oxygen upon laser excitation to kill cancer cells. Both therapies are considered minimum [29] Rapamycin (used as an immunosuppressant) [31] Inserted with lipid-chelated gadolinium (an MRI contrast agent) in the membrane [27] Angioplasty-induced restenosis PLGA nanoparticles Docetaxel (a cytotoxic drug) [33] Poly(amidoamine)-polyvalerolactone nanoclusters JQ1 (an endothelium-protective epigenetic inhibitor) [34] Myocardial ischemia and reperfusion injuries PLGA nanoparticles Secretome of cardiac stem cells (promote cardiac repair and regeneration) [36] Ischemic stroke Sulfur hexafluoride gas Sulfur hexafluoride gas [38] Dextran nanoparticles ZL006e (a neuroprotectant) and rtPA (a thrombolytic drug) [39] Iron oxide (γ-Fe 2 O 3 ) nanoparticles L-arginine (a precursor for biosynthesis of nitric oxide gas) [40] Pulmonary embolism Gold nanorods Urokinase plasminogen activator (a thrombolytic drug) [47] PLGA nanoparticles rtPA [44] invasive for cancer treatment. Recently, verteporfin, a photodynamic agent, was encapsulated into PLGA nanoparticles and coated with platelet membrane (denoted as "NP-Ver@P") for cancer PDT.…”
Section: Targeting Cancer Cells For Cancer Treatment and Detectionmentioning
confidence: 99%
“…Meanwhile, PDT uses the photosensitizers to generate singlet oxygen upon laser excitation to kill cancer cells. Both therapies are considered minimum [29] Rapamycin (used as an immunosuppressant) [31] Inserted with lipid-chelated gadolinium (an MRI contrast agent) in the membrane [27] Angioplasty-induced restenosis PLGA nanoparticles Docetaxel (a cytotoxic drug) [33] Poly(amidoamine)-polyvalerolactone nanoclusters JQ1 (an endothelium-protective epigenetic inhibitor) [34] Myocardial ischemia and reperfusion injuries PLGA nanoparticles Secretome of cardiac stem cells (promote cardiac repair and regeneration) [36] Ischemic stroke Sulfur hexafluoride gas Sulfur hexafluoride gas [38] Dextran nanoparticles ZL006e (a neuroprotectant) and rtPA (a thrombolytic drug) [39] Iron oxide (γ-Fe 2 O 3 ) nanoparticles L-arginine (a precursor for biosynthesis of nitric oxide gas) [40] Pulmonary embolism Gold nanorods Urokinase plasminogen activator (a thrombolytic drug) [47] PLGA nanoparticles rtPA [44] invasive for cancer treatment. Recently, verteporfin, a photodynamic agent, was encapsulated into PLGA nanoparticles and coated with platelet membrane (denoted as "NP-Ver@P") for cancer PDT.…”
Section: Targeting Cancer Cells For Cancer Treatment and Detectionmentioning
confidence: 99%
“…Furthermore, the release of L-arginine at ischemic lesions promoted vasodilation and the thrombosis was disrupted to restore the blood flow. This study showed that PAMNs may be a useful tool for both MRI imaging and targeted therapy for ischemic stroke [ 61 ].…”
Section: Nanomedicine In Stroke Treatmentmentioning
confidence: 99%
“…In a recent study, platelet membrane vesicles (PMVs) were exploited as a specific thrombus-targeting strategy for the treatment of ischemic stroke. PMVs, which have inherited targeting ligands to thrombus and nearby endothelial cells, can specifically bind to the thrombus [ 249 ]. These PMVs loaded with natural compound and magnetic NPs can reach the stroke-induced damaged sites faster and more active when external magnetic fields are applied near the damaged sites, because of the magnetic guidance effect.…”
Section: Various Nanocarriers Containing Natural Compounds For Thementioning
confidence: 99%
“…These PMVs loaded with natural compound and magnetic NPs can reach the stroke-induced damaged sites faster and more active when external magnetic fields are applied near the damaged sites, because of the magnetic guidance effect. Thus, biomimetic exosomes can be promising nanocarriers exhibiting specific neuroinflammation-targeting delivery with the application of external magnetic field or HIFU or extra surface functionalization [ 249 , 250 ].…”
Section: Various Nanocarriers Containing Natural Compounds For Thementioning
confidence: 99%